Spiritual And Psychological Health Of Malaysian Youths - Imam, Syed S. (Research in the social scientific study of religion, 2009)
The purpose of this study was to assess the magnitude of and association between measures of spiritual and psychological health in a sample of 358 undergraduate students of International Islamic University Malaysia (Mean age = 22.25 years, SD = 1.87). All the study variables correlated significantly positive with each other. Significant gender difference existed in terms of mean life satisfaction scores only, with females more satisfied than males. Overall, spiritual well-being predicted self-efficacy, self-esteem, and life satisfaction significantly. Surprisingly, existential well-being predicted self-efficacy, self-esteem, and life satisfaction significantly, whereas religious well-being failed to do so. Discussion includes implications of the present findings for counseling practice and guidelines for future research.